Isolation of a novel soil fungus VT-NSK capable of utilizing the distillery spentwash and synthetic melanoidin – a preliminary report - Kumar, Neethu S; B, Kavitha; T A, Jayanthi; V, Thankamani (Research in Biotechnology, 2012)
Soil samples collected from Mc DowellÃ¢â‚¬â„¢s Distillery Ltd, Aleppey, India were screened for potent melanoidin degrading fungus. Seven fungi were obtained in pure culture. Out of the seven isolates obtained, one strain showing highest rate of melanoidin degradation was coded as VT-NSK and was characterized in detail. The isolate VT-NSK was systematically identified by microscopy, phylogeny by molecular techniques like 18 S rRNA gene sequencing followed by Blast analysis. The isolate VT-NSK was further screened for the melanoidin degrading activity on 1% synthetic melanoidin and 10% distillery effluent amended Czapek dox medium. The isolate showed a decolourization zone of 61mm diameter in 1% synthetic melanoidin and 69mm diameter in 10% distillery effluent amended czapek dox medium after 48hours of incubation. 18S r RNA gene sequencing of the isolate showed maximum alignment with Cunninghamella blakesleeana sp belonging to zygomycetes class. The sequence has been deposited in GenBank with Accession numberÃ‚Â JN570507.